1992
DOI: 10.1073/pnas.89.10.4314
|View full text |Cite
|
Sign up to set email alerts
|

Development of antibodies against the rat brain somatostatin receptor.

Abstract: Somatostatin (SRIF) is a neurotransmitter in the brain involved in the regulation of motor activity and cognition. It induces its physiological actions by interacting with receptors. We have developed antibodies against the receptor to investigate its structural properties. Rabbit polyclonal antibodies were generated against the rat brain SRIEF receptor. These antibodies (F4) were able to immunopeipitate solubilized SRIF receptors from rat brain and the cell line . The specificity of the interaction of these a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

1993
1993
1999
1999

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 18 publications
(37 reference statements)
1
10
0
Order By: Relevance
“…The lack of mRNA encoding the different cloned SRIF receptors and the low levels or absence of SSTR2 immunoreactivity in the striatum suggests that this brain region may express a novel SRIF receptor subtype that has not been cloned . Consistent with this hypothesis, we (Theveniau et al ., 1992) generated polyclonal antiserum against partially purified rat brain SRIF receptors that strongly reacted with a rat striatal SRIF receptor. This polyclonal antiserum does not cross-react with any of the cloned SRIF receptors (M. A .…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…The lack of mRNA encoding the different cloned SRIF receptors and the low levels or absence of SSTR2 immunoreactivity in the striatum suggests that this brain region may express a novel SRIF receptor subtype that has not been cloned . Consistent with this hypothesis, we (Theveniau et al ., 1992) generated polyclonal antiserum against partially purified rat brain SRIF receptors that strongly reacted with a rat striatal SRIF receptor. This polyclonal antiserum does not cross-react with any of the cloned SRIF receptors (M. A .…”
Section: Discussionsupporting
confidence: 85%
“…Theveniau and T. Reisine, unpublished results), indicating that it recognizes a novel SRIF receptor subtype . The further identification of the rat striatal SRIF receptor should be clarified after its cloning, possibly through the use of our recently developed polyclonal antiserum (Theveniau et al, 1992) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies by Gonzalez et al (1989) reported transient expression of ]SRIF binding sites early in cerebellar development. In the present study, we have investigated the developmental pattern of expression of SRIF receptors in the cerebellum and other rat brain regions by using our recently developed antibody against a 60-kDa rat brain SRIF receptor to detect the receptor by immunoblotting (Theveniau et al, 1992). This approach allows us to determine whether qualitative changes occur in receptor level as well as whether physical changes occur in the receptor during development.…”
mentioning
confidence: 99%